(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article scientifically reveals the methods of developing logical thinking of students with the help of modern technologies in education. In addition, the development of education in developed foreign countries is defined as the main task, the role of pedagogical technologies in the organization of the educational process, increasing the interest and aspirations of students to master subjects with the help of pedagogical influence, the main tasks of pedagogical technology , by means of which issues such as the development of students’ thinking, logical thinking abilities, aspects of pedagogical technologies, components of pedagogical technology are analyzed and scientifically based.